2019
DOI: 10.3390/pathogens8030106
|View full text |Cite
|
Sign up to set email alerts
|

Airway Epithelial Derived Cytokines and Chemokines and Their Role in the Immune Response to Respiratory Syncytial Virus Infection

Abstract: The airway epithelium is the primary target of respiratory syncytial virus infection. It is an important component of the antiviral immune response. It contributes to the recruitment and activation of innate immune cells from the periphery through the secretion of cytokines and chemokines. This paper provides a broad review of the cytokines and chemokines secreted from human airway epithelial cell models during respiratory syncytial virus (RSV) infection based on a comprehensive literature review. Epithelium-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 154 publications
2
48
1
4
Order By: Relevance
“…It is now understood that respiratory cilia share chemosensory abilities once thought unique to primary cilia, long known to be involved in chemosensation, signal transduction, and regulation of cellular growth (51,87,122,146,170). Studies have also shown possible involvement of cilia in lung repair processes (148,155) and in regulating cytokine and antimicrobial production (11,56,131), thus suggesting an even greater involvement of these organelles in lung function than initially thought. Studies by our group and others have shown that airway cilia express members of the bitter taste family of receptors (T2Rs) that may hold functional importance in airway innate immunity against bacterial infections by driving innate immune defenses in response to bacterial antigens (52,65,113,170).…”
Section: Respiratory Cilia: Structure Function and Expressionmentioning
confidence: 99%
“…It is now understood that respiratory cilia share chemosensory abilities once thought unique to primary cilia, long known to be involved in chemosensation, signal transduction, and regulation of cellular growth (51,87,122,146,170). Studies have also shown possible involvement of cilia in lung repair processes (148,155) and in regulating cytokine and antimicrobial production (11,56,131), thus suggesting an even greater involvement of these organelles in lung function than initially thought. Studies by our group and others have shown that airway cilia express members of the bitter taste family of receptors (T2Rs) that may hold functional importance in airway innate immunity against bacterial infections by driving innate immune defenses in response to bacterial antigens (52,65,113,170).…”
Section: Respiratory Cilia: Structure Function and Expressionmentioning
confidence: 99%
“…The respiratory epithelium is an important driver of the immune response against respiratory viruses, as these cells are implicated in the secretion of large quantities of chemokines upon infection. This will attract immune cells to the site of infection, as well as other various cytokines that modulate the immune response [ 267 ].…”
Section: Role Of the Respiratory Epithelium During The Immune Respmentioning
confidence: 99%
“…For hRSV, epithelial cells have been seen to contribute to the promotion of local inflammation and angiogenesis, the recruitment of various inflammatory cell types, and the development of a harmful T H 2 adaptive immune response. Many of these studies are based on in vitro models, and we only discuss the secretion of cytokines that have been observed in at least one type of human primary cell culture [ 118 , 230 , 247 , 267 , 268 , 269 , 270 , 271 , 272 , 273 , 274 , 275 , 276 , 277 , 278 , 279 , 280 , 281 , 282 , 283 , 284 , 285 , 286 , 287 , 288 , 289 , 290 , 291 , 292 , 293 , 294 , 295 , 296 , 297 , 298 ].…”
Section: Role Of the Respiratory Epithelium During The Immune Respmentioning
confidence: 99%
“…RSV infection induces upregulation of a variety of cytokines in the nasal mucosa of older adults. Mucosal cytokine production plays an important role in modulation of the (protective or pathogenic) immune response to RSV (17). However, few data are available on the local cytokine response in the older adult population specifically (9).…”
Section: Fig 2 Serologic Analyses Of Rsv-infected Participants and Comentioning
confidence: 99%